Fatores associados à síndrome da fragilidade em mulheres idosas - Clóris Regina Blanski Grden; Vanessa Regina de Andrade; Luciane Patrícia Andreani Cabral; Péricles Martim Reche; Erildo Vicente Muller; Pollyanna Kássia de Oliveira Borges (Universidade Federal do Ceará, 2017)
Objective: to evaluate the factors associated with frailty syndrome in elderly women in an outpatient clinic. Methods: cross-sectional study with 252 elderly women. The Mini Mental State Examination and the Edmonton Frail Scale were applied. The association of variables was performed using simple linear regression (Fisher's F and Student's t tests), p≤0.05. Results: there was prevalence of married women (44.4%) with low schooling (50.0%) and living with relatives (50.8%). Among them, 28.6% had mild, 13.0% moderate and 3.6% severe frailty. The factors associated with the syndrome were age (p=0.021), level of education (p=0.001), living with relatives (p=0.013), illnesses (p=0.023), falls (p=0.001) and hospitalization in the last 12 months (p=0.001). Conclusion: evidenced that almost half of the sample presented some type of frailty. Thus, it is important to evaluate this population frequently, considering the associated factors that can contribute to frailty.